A separation axiom between semi-T° and semi-T1 - Caldas, Miguel (Pontificia Universidad Católica del Perú, 1997)
The author introduces a new separation axiom and studies some of their basic properties. The implication of these new separation axiom among themselves and with the well known axioms semi-T2 semi-T1 and semi-T0 are obtained.
Keywords: Espacios Topológicos; https://purl.org/pe-repo/ocde/ford#1.01.00